(untitled) (European Journal of Pure and Applied Mathematics, 2017)
‎Finsler s-manifolds are a generalization of Riemannian‎ ‎s-manifolds‎. ‎An important property of such manifolds is the‎ ‎homogeneity‎. ‎In this paper we study Finsler s-manifolds‎. ‎We‎ ‎first construct some example of Finsler s-manifolds which are‎ ‎neither Riemannian nor symmetric‎. ‎Then we consider symmetric‎ ‎preserving diffeomorphism of Finsler s-manifolds‎. ‎Finally we‎ ‎give some algebraic and existence theorem of these spaces‎.